The Project for Youth and Adults Education in Agrarian Reform Settlements in Piauí state (Proejapi) in the context of Pronera - Jullyane Frazão Santana; Rosana Evangelista da Cruz; Marli Clementino Gonçalves (Universidade Federal do Norte do Tocantins, 2021)
The National Agrarian Reform Education Program has advanced in relation to the policies historically developed in Brazil for the education of countryside populations, representing a paradigm shift. This article was directed by the following research problem: how did the implementation of Pronera materialize in the State of Piauí, through the Youth and Adult Education Project of Agrarian Reform Settlements? The objective is to analyze the Pronera implantation process in the State. The investigation was based on literature review, document analysis and interviews with different subjects from the institutions and movements involved in the implementing process of the Program. The results indicate that this process involved difficulties related to the structural precariousness of the settlements; the level of monitors training; the bureaucratic aspects of the process processing; the discontinuity in the release of the installments agreed in the work plans and the delay in pedagogical activities, elements that interfered in the dynamics of the Project's execution. The problems faced were being overcome by the engagement of the pedagogical team and the social and union movements involved, revealing that Pronera played a central role in expanding the processes of schooling and training of the people engaged in the struggles for the right to education and social transformation.